Interdisciplinaridade ou puzzle disciplinar? uma investigação em um curso de Letras/Inglês - Carvalho, Eliana Márcia dos Santos (2014)
This research in Applied Linguistics has two goals: to investigate the applicability of interdisciplinary actions in the university and to confront the concepts of interdisciplinarity by graduation teachers with the conceptions indicated in the Pedagogic Project of university course. Throughout this writing I tried to answer questions about the nature of teaching actions of a College degree in English Language Teaching that has a curriculum guided by the interdiciplinarity approach. Although there still no a ready definition to the term interdisciplinarity, the teachers conceptions were the main point to do a confrontation with the actions developed in the College Course. The interdisciplianrity approach is the focus of this work. The research has as its context the reality of a College degree in English Language Teaching from a multicampi University in the Brazilian Northeast . The developed studies provided an understanding of interdisciplinarity not as a "disciplinary puzzle", but as an educational attitude where personal, academic and methodological interconnections are possible. The methodology adopted was based on Ricoeur s hermeneutic (1990, 2006), where it was possible change as texts the interview and the questioner, instruments used to collect the information supporting this research. The teachers actions of the College degree in English Language from the campus focused refers to the to the field of interdisciplinary postulated by Japiassu (1976), Fazenda (1979, 2008, 2011, etc.), Pombo (1993, 2011). The study of História da Filosofia das Ciências in Lisboa-PT made me understand the interdisciplinarity as the current manifestation of the unity of science in school. The interpretation of texts from the questionnaires and interviews based on the pillars consistency, humility, expecting, detachment and respect - that guide interdisciplinary attitude, expresses an urgent necessity for curriculum reform and change of attitude in the educational environment